Instrumen Self-Compassion Usia Remaja (ISCIRA): Analisis Model Rasch - Sari, Lyana Alvionita; Nurihsan, Juntika; Yustiana, Yusi Riksa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Self-compassion is an individual's effort to open up, connect with pain, and treat oneself well, even under challenging circumstances. Various studies continue to develop regarding self-compassion, but the limitation of the instrument, specifically for adolescents' age, becomes the study's concern. This study aims to develop the Instrumen Self-Compassion Usia Remaja (ISCIRA) using the RASCH measurement model. Participants in this study were 243 high school students aged 14-17 years. The results of the Instrumen Self-Compassion Usia Remaja (ISCIRA) have a reliability value in the excellent category and an item reliability value of 0.98 in the particular category. The validity of the 54 items in the Instrumen Self-Compassion Usia Remaja (ISCIRA)was tested, and the results obtained were 44 statement items suitable for measuring adolescent self-compassion.